The Kinetic Effect of Some Wine Components on the Enzymatic Hydrolysis of β-glucan - Zinnai, A.; Venturi, F.; Quartacci, M.F.; Andreotti, A.; Andrich, G. (South African Journal of Enology and Viticulture, 2016)
Enzymatic preparations containing β-glucanases are utilised extensively in winemaking to facilitate the filtration of musts and wines coming from grapes affected by Botrytis cinerea, and to induce the release of mannoproteins and oligosaccharides from the cell walls of yeasts. The aim of the present work was to investigate the possible inhibitory effect of some wine components, and in particular of ethanol, on β-glucanase activities. For this purpose, the kinetic activity of a commercial enzymatic preparation containing β-glucanases was tested utilising both model solutions (buffer solution having a pH value similar to a must/wine with or without 13% v/v of ethanol added) and a red wine. When ethanol was added to the model solution, both the kinetic constant k and glucose production suffered a decrease of about 50% compared to the values detected in the absence of ethanol. A further loss of activity (about 87%) was found using red wine as reaction medium, suggesting, as already reported in the literature, that phenols could add their inhibitory effect to that of ethanol. The results obtained provide useful suggestions that can be adopted during winemaking. To promote the hydrolysis of the possible excess of β-glucan coming from grapes affected by Botritis cinerea, it would be more convenient to add β-glucanases before a significant amount of ethanol accumulates in the must/wine, while it is not possible to avoid the negative impact of ethanol or other possible inhibitors (phenols) to promote yeast degradation in wine left on lees.